Great expectations [videorecording (DVD)] - Irvine, Jeremy, 1990-; Coltrane, Robbie; Bonham Carter, Helena, 1966-; Fiennes, Ralph; Dickens, Charles, 1812-1870 (Twentieth Century Fox Home Entertainment, 2014)
After Pip, an orphaned blacksmith's apprentice inherits a fortune from an anonymous benefactor, his future seems promising. But a bitter heiress is intent on preventing Pip from finding true love.